Impact of thinning the GaN buffer and interface layer on thermal and electrical performance in GaN-on-diamond electronic devices. (31st January 2019) - Middleton, Callum; Chandrasekar, Hareesh; Singh, Manikant; Pomeroy, James W.; Uren, Michael J.; Francis, Daniel; Kuball, Martin
Abstract: We demonstrate that GaN-on-diamond technology with an ultra-thin GaN buffer and interface layer offers excellent thermal resistance alongside good electrical performance. Two device sets were investigated, one with 354 nm thick GaN buffer and 17 nm thick interface layers, the other with 700 nm thick GaN buffer and 36 nm thick interface layers. The samples demonstrate excellent thermal resistances of 9 ± 1 K/(W/mm) and 10.0 ± 0.5 K/(W/mm), respectively. Trade-offs between GaN buffer thickness and effective thermal boundary resistance are discussed demonstrating pathways for the advancement of GaN-on-diamond technology. IV measurements show low trapping and reduced thermal non-linearity in devices with ultra-thin GaN layers.